Kerja Kode dalam Iklan Ramayana Ramadhan #KerenLahirBatin - Rizky Noviasri (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2018)
Ramayana Ramadhan #Kerenlahirbatin commercial is a video advertisement that get much public attention. It can be seen in numbers of views of this video in Ramayana Youtube Channel that reach more than ten million and still counting in a short period. This commercial is fascinating because it shows a humorous side that difference from others. Using code analysis based on the five codes theory of Roland Barthes’s, researcher reveal the works of codes that delivers humorous effect in the commercial. It happen because there are kinds of code that misused, double coding, overcoding, even it brings up a new code. The code playfulness in this commercial is the main principe of intertextuality that lead into kitsch idiom. Keywords : Code, Advertisement, Intertextuality, Kitsch